Mechanism of translation of monocistronic and multicistronic human immunodeficiency virus type 1 mRNAs. - Schwartz, S (1992)
We have used a panel of cDNA clones expressing wild-type and mutant human immunodeficiency virus type 1 (HIV-1) mRNAs to study translation of these mRNAs in eucaryotic cells. The tat open reading frame (ORF) has a strong signal for translation initiation, while rev and vpu ORFs have weaker signals. The expression of downstream ORFs is inhibited in mRNAs that contain the tat ORF as the first ORF. In contrast, downstream ORFs are expressed efficiently from mRNAs that have rev or vpu as the first ORF. All env mRNAs contain the upstream vpu ORF. Expression of HIV-1 Env protein requires a weak vpu AUG, which allows leaky scanning to occur, thereby allowing ribosomes access to the downstream env ORF. We concluded that HIV-1 mRNAs are translated by the scanning mechanism and that expression of more than one protein from each mRNA was caused by leaky scanning at the first AUG of the mRNA.